A meta‐analysis on the cardiac safety profile of domperidone compared to metoclopramide. Issue 9 (1st November 2018) - Bor, Serhat; Demir, Mesut; Ozdemir, Oktay; Yuksel, Kivanc
Abstract : Background: This meta‐analysis aimed to assess the cardiac safety profile of domperidone treatment for the risk of cardiovascular (CV) event and QT prolongation. Methods: Data from nine studies involving 101, 155 patients were used for the analysis of CV event risk, while data from eight studies involving 390 patients were used for the analysis of QT prolongation risk. Results: Meta‐analysis findings suggested a significant increase in CV risk under domperidone as compared to no treatment for domperidone doses of >30 mg/day (OR: 3.14, 95% CI, 1.191 to 8.304, p  = 0.021), no significant increase in QT prolongation event rates with domperidone (3.54%, 95% CI, 1.73% to 7.10%) and a significantly lower CV risk for domperidone than for metoclopramide (OR: 0.63, 95% CI, 0.58 to 0.70, p  < 0.001). Conclusions: The present meta‐analysis indicates that domperidone treatment may not be associated with an overall CV event risk increase at doses ≤30 mg/day and does not result in QT prolongation.